2016
DOI: 10.4238/gmr.15038377
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of LTβR and differential expression in Escherichia coli F18 resistant/sensitive piglets

Abstract: ABSTRACT. We analyzed LTβR mRNA expression in piglets from birth to weaning and compared the differential expression between Escherichia coli F18-resistant and sensitive populations to determine whether this gene could be used as a genetic marker for E. coli F18 resistance. Sutai piglets of different age groups (8, 18, 30, and 35 days; N = 4 each) and piglets demonstrating resistance/sensitivity to E. coli F18 were used. LTβR expression levels were determined by real-time PCR. The LTβR expression levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…LTβR is reportedly highly expressed in the lymph nodes, duodenum and jejunum of eight-day-old newborn piglets, which may be beneficial for developing resistance to E. coli F18 in pigs [ 21 ], and IPEC-J2 cells are susceptible to PEDV infection [ 22 ]. As such, we investigated the effects of LTβR on PEDV infections in IPEC-J2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LTβR is reportedly highly expressed in the lymph nodes, duodenum and jejunum of eight-day-old newborn piglets, which may be beneficial for developing resistance to E. coli F18 in pigs [ 21 ], and IPEC-J2 cells are susceptible to PEDV infection [ 22 ]. As such, we investigated the effects of LTβR on PEDV infections in IPEC-J2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…LTβR signaling is required for clearance of Salmonella typhimurium in infected gut lumen [ 28 ]. Additionally, very recent data showed that LTβR is highly expressed in the lymph nodes, duodenum and jejunum of eight-day-old newborn piglets, which may be beneficial for developing resistance to E. coli F18 in pigs [ 21 ]. In addition, the role of LTβR in viral infection was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified the differential expression of the FUT2 , FUT3 , TLR5 , TAP2 , IL1β genes in the duodenum, indicating that these genes probably play a crucial role in the resistance to E. coli F18. Our previous studies concentrated on the relationship of immune gene expression and E. coli F18 resistance in pigs [ 4 , 5 , 6 , 7 , 8 ], only a few reports directly on receptor formation showing the effect of the α(1,2) fucosyltransferase 1 ( FUT1 ) gene M307 G/A mutation on the adhesion of E. coli F18 to pig intestinal epithelial cells [ 9 ], but its polymorphism distribution in more than 20 Chinese local pig breeds and wild boar population is extremely skewed [ 10 , 11 , 12 ]. The smallest antigenic determinant of the E. coli F18 receptor is the type 1 H-antigen of the ABO blood group antigens [ 13 ].…”
Section: Introductionmentioning
confidence: 99%